Measuring the Sedimentation Rate of Red Blood Cells in Infected Camels with Respiratory Disease like Pneumonia, Bronchitis and inflammation of Lung - Zahra M Al-Hakak (Journal of Global Pharma Technology, 2017)
The objective of this study is to determine sedimentation rate of red blood cells in Iraqi camels   and compare the value between diseased and healthy animals. A total of 150 samples of blood were collected from Iraqi camels. All samples were collected randomly from both sexes and from different ages ranged from (less than a year-15 years) .Some camels were suffering from different diseases and injuries. The study included: 1. General knowledge examination: (age of the animal - type of animal - color - history of the condition - drugs and vaccines used and the method of grazing). 2. Clinical examination included: (check the temperature - the speed of the pulse and breathing - auscultation of the heart by stethoscope - check covering of skin). 3. Measure the sedimentation rate of red blood cells (ESR) through three hours. Results showed a clinical examination that there are (45) animal was suffering from various diseases and (105) animal healthy. The results of the examination (ESR) values ranged in healthy animals in the first hour (0.33-1.6) mm / h ,in the second hour (1.56 -2.3) mm / h and in the third hour (2.66-3.44) mm / h While in sick camels the results of the examination (ESR) values ranged in the first hour (1.75-5) mm / h ,in the second hour (5 -13.5) mm / h and the third hour (7.75-19.5) mm / h .The test results showed that (ESR) higher in animals that were suffering from the disease showed a statistical significant level of difference (0.05> P) between healthy and diseased camels .Recommendations The study recommended that must be done with many other studies on the blood of camels to the lack of such a research in Arab library, deepen the field studies on camels and must be supported by the state and specialists.Keywords: Red blood cells, Sedimentation Rate, Pneumonia, Bronchitis, Camels, Iraq.